Microstructural characterization of cobalt chromium (ASTM F75) cubes produced by EBM technique - Chauhan, Mandeep (My University, 2017)
Cobalt-chromium based alloys have been widely used to make biomedical implants for hip and knee joints. The alloy enables to manufacturing metal on metal bearing implants which have increased life and minimum wear debris generated. They have excellent corrosion resistance, wear resistance, high stiffness and high mechanical strength properties. In the past, the alloy implants have been manufactured by investment casting method. However, dental casting implants have been reported to have fractured occasionally on small plastic deformation. In recent years, additive manufacturing by electron beam melting (EBM) technique has been used to manufacture complex design implants with short lead times and minimum post machining. The alloy consists of two primary phases: a high temperature γ-face centered cubic (-fcc) phase which shows high elongation and ultimate tensile strength, other is low temperature ε-hexagonal close packed (-hcp) phase which shows low elongation and brittle fracture on straining. Carbon (max. 0.35 wt. %) and nitrogen (max. 0.25 wt. %) are two important trace elements added to increase mechanical strength, elongation and wear resistance of the alloy. They inhibit ε-hcp to γ-fcc phase transformation and provide solid solution and precipitation strengthening. However, increased concentration of precipitates in the form of carbides and nitrides have reported to decrease tensile elongation and strength. Researchers have concentrated their efforts to find the correct alloy composition and heat treatment to stabilize γ-fcc phase matrix and increase strength for casting and hot forging process. However, little work has been done to optimize alloy composition for EBM technique. With the EBM technique, the alloy is reported to give gassing of carbon and nitrogen compounds that erode the cathode and it requires expensive post heat treatment to increase ductility. It was important to understand the effect of carbon and nitrogen content on microstructure and on corresponding mechanical properties for cobalt-chromium alloy parts manufactured by EBM technique. This thesis investigates the microstructural characteristics of the cubes with varying carbon and nitrogen content under as-built and hot isostatic pressing conditions. The microstructures were evaluated using optical microscopy, scanning electron microscopy including electron back scattered diffraction analysis, and X-ray diffraction. The obtained microstructures are then compared with mechanical tensile test data.
Keywords: Materialvetenskap; Materialteknik; Metallurgi och metalliska material; Metallurgisk process- och produktionsteknik; Materials Science; Materials Engineering; Metallurgy and Metallic Materials; Metallurgical process and manufacturing engineering